Protective Effect of Goat Kefir on Arsenic-Induced Ovarian Oxidative Stress in Female Rats - Nur Aisyah Laily (Journal of Global Pharma Technology, 2020)
Objective: To determine the role of goat kefir in ovarian protection from arsenic-induced ovarian oxidative stress. Methods: twenty female wistar rats were randomly divided into five groups; one group was treated as control, one group was treated with arsenic 2 mg/kg/day only, while three groups were treated with different doses (1.25, 2.5, 5 mL/kg/day) of goat kefir and arsenic for 35 days. After 35 days, the rats were terminated, then the ovaries were taken for analysis of MDA levels and SOD activity using spectrophotometry. Results: arsenic exposure significantly increased MDA levels but did not significantly decrease ovarian SOD activity compared to the control group. Kefir administration at doses of 1.25 and 2.5 mL/kg/day could reduce ovarian MDA levels although it was not statistically significant. However, MDA levels were greater in the 5 mL/kg/day group than the arsenic-only group. Kefir increased ovarian SOD activity at all three doses although it was not statistically significant. Conclusion: goat kefir was able to reduce MDA levels and increase ovarian SOD activity in rats that were exposed to arsenic although it was not statistically significant.